Analisis Usability Website MA Taruna Teknik Al Jabbar Menggunakan Metode SUS - Damanik, Najwa Alifah Zulfikar; Sari, Mira Fathilla (Jurnal Sains dan Teknologi (JSIT), 2026)
Digital transformation in educational institutions demands functional and optimal information platforms. This study evaluates the usability of the MA Taruna Teknik Al Jabbar Medan website using the System Usability Scale (SUS) with a quantitative approach involving students and teachers. Results show an average score of 60.1, placing the platform in Grade D (Marginal Low). While functional, the website requires optimization in navigation consistency and interface design. These findings provide strategic recommendations for design restructuring to enhance user experience and digital information delivery effectiveness.